Sistem Pakar Pemilihan Bibit Padi Unggul dengan Metode Forward Chaining - Efan, Efan; Sasmita, Sasmita; Suhada, Desmi Aulia (Journal of Computer System and Informatics (JoSYC), 2024)
Expert systems are technologies that are widely used in the agricultural sector, one of which is for selecting seeds. Rice is one of the most important food crops in life, rice is the main source of carbohydrates for the majority of the world's population. One of the important factors influencing the growth of rice production is better and better quality seed so that it can increase the productivity of rice plants, using better seed can increase yields up to three times a year. This research aims to develop an efficient system for selecting superior payi seeds using the Forward Chaining method, in order to assist the mappers in selecting payi seeds that are in accordance with their criteria. This research was motivated by the process of selecting rice seeds by farmers who still had little knowledge about rice and was carried out by asking people who only understood rice. The system development method uses the Waiter Faill method, which Taihaipain uses, including analysis, design, coding and testing, uses the system using Axure applications, StarUML for development, Visual Studio Code applications for coding, PHP, HTML for programming skills, and Database XAMPP and MySQL. The testing method uses the Blackbox Testing method, namely to determine whether the functionality, input and output of the software meets the required specifications. The results of the research show that all application features function well after being tested using the black box testing method. This expert system also helps the community in choosing rice seeds, as shown through interviews that 85% of respondents need this system.